Legal Memorandum on the Legal Protection of Consumers on the Use of Exoneration Clauses by Transportation Services of Rosalia Indah Bus Company in the Case of Theft of Goods Reviewed Based on Consumer Protection Law - Zachra, Kintan Prameswari Aradea (CV. Publikasi Indonesia, 2024)
This research examines the legal protection for consumers in cases involving the use of exoneration clauses by transportation services, specifically focusing on PO Rosalia Indah's bus service. Exoneration clauses, which limit a company's liability in the event of theft or loss of goods, raise significant concerns regarding consumer rights. This study evaluates whether such clauses comply with Indonesia’s Consumer Protection Law and identifies the legal remedies available to consumers affected by such provisions. The research employs a normative juridical method, analyzing legal texts, including Law No. 8/1999 on Consumer Protection and relevant court rulings, to determine the legality and enforceability of exoneration clauses in transportation agreements. Data were collected through literature reviews of legal documents, journals, and cases related to consumer protection in transportation services. The results indicate that the exoneration clauses used by PO Rosalia Indah violate the principles outlined in the Consumer Protection Law, particularly Article 18, which prohibits businesses from including provisions that reduce consumer rights. It was also found that consumers have the right to pursue compensation through litigation or non-litigation mechanisms, such as the Consumer Dispute Settlement Agency (BPSK). The study concludes with recommendations for enhancing legal frameworks and ensuring that consumer rights are adequately protected in transportation service agreements.